Othello - Mulherin, Jennifer; Frost, Abigail (Bath, Avon : Cherrytree Books, 1990)
Presents a plot synopsis, character sketches, and quotations from each of ten plays, plus a brief biography of William Shakespeare.
A midsummer night's dream -- The merchant of Venice -- As you like it -- Twelfth night -- Romeo and Juliet -- Julius Caesar -- Macbeth -- Hamlet -- King Lear -- Othello.
Originally published: Slough, Berkshire : Cherrytree Press, 1993.
Includes index.
Keywords: Shakespeare, William, -- 1564-1616 -- Adaptations -- Juvenile literature; Shakespeare, William, -- 1564-1616 -- Adaptations